2003
DOI: 10.1046/j.1365-2958.2003.03517.x
|View full text |Cite
|
Sign up to set email alerts
|

Translational repression mechanisms in prokaryotes

Abstract: SummaryTranslational repression results from a complex choreography of macromolecular interactions interfering with the formation of translational initiation complexes. The relationship between the rate and extent of formation of these interactions to form repressed mRNA complexes determines the extent of repression. A novel analysis of repression mechanisms is presented here and it indicates that the reversibility of repressed complex formation influences the steady state balance of the distribution of transl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 43 publications
1
47
0
2
Order By: Relevance
“…It was proposed that the entrapment mechanism would sustain rather weak binding affinities of protein-mRNA complex. 18,19 In agreement with this observation, the binding affinity of EcS15 is about one order of magnitude lower than that for its 16S rRNA binding site and of TtS15 for its mRNA target. In B. stearothermophilus (Fig.…”
Section: Plasticity Of Mrna-regulatory Protein Recognition In Translasupporting
confidence: 73%
“…It was proposed that the entrapment mechanism would sustain rather weak binding affinities of protein-mRNA complex. 18,19 In agreement with this observation, the binding affinity of EcS15 is about one order of magnitude lower than that for its 16S rRNA binding site and of TtS15 for its mRNA target. In B. stearothermophilus (Fig.…”
Section: Plasticity Of Mrna-regulatory Protein Recognition In Translasupporting
confidence: 73%
“…This indicated that the predicted structural conformation between the two genes prevented amplification of complete cDNA during the reverse transcriptase reaction. The efficiency of translational initiation and regulation is strongly correlated with the structure of the ribosomebinding site (RBS) (Schlax & Worhunsky, 2003). The primary interaction between mRNA and the 30S subunit rRNA requires local single-stranded mRNA (Draper, 1987(Draper, , 1996Gualerzi & Pon, 1990;Draper et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The binding of trans-acting proteins and/or antisense RNA to target mRNA can allosterically control translation (reviewed in Ref. 37). As being revealed from our results on hsdA regulation, RepB acts as a trans-acting factor that modulates hsdA expression by repressing 3␣-HSD/CR mRNA translation.…”
Section: Discussionmentioning
confidence: 52%
“…As being revealed from our results on hsdA regulation, RepB acts as a trans-acting factor that modulates hsdA expression by repressing 3␣-HSD/CR mRNA translation. The occurrence of cis-acting mRNA elements in the 3␣-HSD/CR mRNA structure that could repress hsdA translation was additionally excluded by temperature shift experiments of the bacterial cultures from 30 to 42°C (data not shown) (37).…”
Section: Discussionmentioning
confidence: 99%